Characteristics of radial access site coronary procedures in patients with arteria lusoria among 5789 patients undergoing coronary angiography at a primary radial access centre. Issue 1 (11th July 2013) - Gokhroo, Rajendra K; Padmanabhan, Deepak; Bisht, Devendra; Gupta, Sajal
Abstract : Background: Anatomical obstructions are the bane of radial access site for coronary procedures for inexperienced operators. The availability of better hardware in the performance of procedures by this route has mitigated this problem. Arteria lusoria (AL) is a congenital anomaly which predisposes to access site crossover during the early phase of the learning curve. We present our experience in the performance of radial access site coronary angiographies of these patients, which is the first such study reported in literature. Materials and methods: Retrospective analysis of 5879 patients from August 2006 to August 2012 was done with special attention to preprocedural and peri-procedural parameters in patients with AL. Analysis of the angle made by the aberrant vessel with the arch of aorta is also noted. Comparisons were made with timings of radial angiography as reported by Looi et al . Comparison was made of the time taken to complete the procedure by the operator vis-a vis the time taken during earlier performance of the procedure in these patients by the same operator. Results: The incidence of AL is 0.5%. The total time taken for the procedure is 18.1+6.9 min and the total fluoroscopy time needed is 4.0+2.7 min. Comparisons with the study conducted by Looi et al reveal no statistical significance between the times (p>0.05). When stratified with respect to the experience of the performing operator, there was significant difference (p<0.001) in the total time taken and the total fluoroscopy time required for the procedure when performed with experience of previous angiographies via the radial route. The aberrant vessel made an angle of 45° on an average with the arch of aorta. With experience, the number of guiding catheters needed for the procedure decreased from four to one and the operator was able to perform the procedure with the same catheter. Peri-procedural complications of vasospasm and minor bleeds were the only ones to attain statistically significant increase in these patients (p<0.05) and were related to higher duration of the procedure and unrelated to the age and sex of the patient. Conclusions: AL is not a contraindication to the performance of coronary angiography. Experience of the operator helps in achieving procedure and fluoroscopy times akin to that of routine radial angiography.